Mechanical Performance and Interfacial Bonding Mechanism of High-Performance ECC in Steel-Concrete Composite Link Slab in Simply Supported Bridges - Chengquan Wang; Rongyang Liu; Kangyu Wang; Yuhan Liang; Yingjie Ning (Buildings, 2025)
This paper proposes a steel-ECC ordinary concrete composite continuous bridge deck structure to address the cracking problem of simply supported beam bridge deck continuity. Through theoretical and experimental research, a high-performance ECC material was developed. The ECC material has a compressive strength of 57.58 MPa, a tensile strain capacity of 4.44%, and significantly enhanced bending deformation ability. Bonding tests showed that the bond strength of the ECC-reinforcing bar interface reaches 22.84 MPa when the anchorage length is 5d, and the splitting strength of the ECC-concrete interface is 3.58 MPa after 4–5 mm chipping treatment, with clear water moistening being the optimal interface treatment method. Full-scale tests indicated that under 1.5 times the design load, the crack width of the ECC bridge deck continuity structure is ≤0.12 mm, the maximum deflection is only 5.345 mm, and the interface slip is reduced by 42%, achieving a unified control of multiple cracks and coordinated deformation. The research results provide a new material system and interface design standards for seamless bridge design.